Transition‐Metal‐Free Coupling of 1,3‐Dipoles and Boronic Acids as a Sustainable Approach to C−C Bond Formation - Livingstone, Keith (Chemistry, 2020)
The need for alternative, complementary approaches to enable C−C bond formation within organic chemistry is an on‐going challenge in the area. Of particular relevance are transformations that proceed in the absence of transition‐metal reagents. In the current study, we report a comprehensive investigation of the coupling of nitrile imines and aryl boronic acids as an approach towards sustainable C−C bond formation. In situ generation of the highly reactive 1,3‐dipole facilitates a Petasis–Mannich‐type coupling via a nucleophilic boronate complex. The introduction of hydrazonyl chlorides as a complementary nitrile imine source to the 2,5‐tetrazoles previously reported by our laboratory further broadens the scope of the approach. Additionally, we exemplify for the first time the extension of this protocol into another 1,3‐dipole, through the synthesis of aryl ketone oximes from aryl boronic acids and nitrile N‐oxides.